2013
DOI: 10.1016/j.jcin.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Readmission in the 30 Days After Percutaneous Coronary Intervention

Abstract: Readmissions within 30 days due to complications related to PCI performed on index admission are rare (0.9% of all PCI) and are an infrequent cause of readmission (<12% of readmissions). Thirty-day readmission after PCI should not be used as a quality metric of PCI performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
44
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 14 publications
7
44
1
1
Order By: Relevance
“…First, we have shown that evaluations of chest pain or symptoms concerning for angina, by far, constitute the largest proportion of readmissions (38.1%) within 30 days. These results confirm and extend the results of a recent study 9 that found 26.7% of readmissions evaluate chest pain or other symptoms concerning for angina (adding unstable angina, non-ST-segment-elevation myocardial infarction, stable angina, noncardiac chest pain, and pericarditis) and support the generalizability of our findings. Among patients readmitted with chest pain or possible angina, a large proportion received diagnostic imaging during the readmission, with more than half undergoing repeat coronary angiography.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, we have shown that evaluations of chest pain or symptoms concerning for angina, by far, constitute the largest proportion of readmissions (38.1%) within 30 days. These results confirm and extend the results of a recent study 9 that found 26.7% of readmissions evaluate chest pain or other symptoms concerning for angina (adding unstable angina, non-ST-segment-elevation myocardial infarction, stable angina, noncardiac chest pain, and pericarditis) and support the generalizability of our findings. Among patients readmitted with chest pain or possible angina, a large proportion received diagnostic imaging during the readmission, with more than half undergoing repeat coronary angiography.…”
Section: Discussionsupporting
confidence: 92%
“…Although administrative claims databases have been used to categorize readmission discharge diagnoses broadly, [6][7][8] few studies have been conducted using detailed medical record reviews to characterize patient presentations for readmission, the care received or the associated use of resources during these hospitalizations. 9 To address this gap in knowledge, we sought to characterize reasons for 30-day readmission after PCI through detailed exploration of the medical records at 2 hospitals within a large integrated healthcare system. We further examined the use of diagnostic testing and therapeutic procedures for the most common causes of readmission.…”
mentioning
confidence: 99%
“…5 Currently, readmission rates vary widely, ranging from 8% to 15%, and within one state, it varied significantly between hospitals, with some having readmission rates to the index hospital as low as 9% and others as high as 22%. 2,6 The cause of this wide variation is likely multifactorial. Certain patient characteristics and clinical factors such as sex, race, discharge to a nursing home, longer length of stay, certain comorbidities, lack of insurance or Medicare or Medicaid use, and peri-and postprocedural complications have been associated with higher risks of readmission.…”
mentioning
confidence: 99%
“…9 Few readmissions are because of procedural complications, so many PCI readmissions are related to medication choice and management, issues around access to outpatient care, and lack of timely assessment on re-presentation. 6,9 As such, nonprocedural care may substantially affect this procedural metric.…”
mentioning
confidence: 99%
“…In particular, a medical record review of 262 early PCI readmissions at Geisinger Medical Center in Danville, Pennsylvania, demonstrated that only 11.9% of readmissions are related to procedural complications. 12 By contrast, 40.2% of early readmissions were considered unrelated to the index admission, including noncardiac chest discomfort. A similar analysis within the Partners Healthcare system in Boston, Massachusetts, demonstrated compatible results with only 6.7% of readmissions related to procedural complications and 38.1% of readmissions for chest discomfort or other symptoms concerning for angina without immediately obvious stent thrombosis.…”
Section: Limitations Of the Pci Readmission Performance Metricmentioning
confidence: 99%